2016
DOI: 10.1016/j.seizure.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Status epilepticus secondary to glioma

Abstract: SE secondary to glioma responded well to treatment and should be treated aggressively regardless of the oncological prognosis. Seizures during tumor progression were not more treatment refractory than SE in patients with stable glioma disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…The appearance of tumor-associated status epilepticus (TASE) can indicate tumor progression [5,15]. In half of the patients with glioma, status epilepticus is due to other factors such as non-adherence to medication or intercurrent conditions, for instance infections or electrolyte disturbances [16]. A study from 2021 showed that the semiology of TASE was more commonly complex focal (74%) and less commonly generalized convulsive (17%) [5].…”
Section: Status Epilepticusmentioning
confidence: 99%
“…The appearance of tumor-associated status epilepticus (TASE) can indicate tumor progression [5,15]. In half of the patients with glioma, status epilepticus is due to other factors such as non-adherence to medication or intercurrent conditions, for instance infections or electrolyte disturbances [16]. A study from 2021 showed that the semiology of TASE was more commonly complex focal (74%) and less commonly generalized convulsive (17%) [5].…”
Section: Status Epilepticusmentioning
confidence: 99%
“…In contrast to TAE, TASE is more responsive to AED therapy and is managed by first-line AEDs like phenytoin and benzodiazepines [52]. It was also shown that TASE is as responsive to drug therapy as is status epilepticus occurring in the general population [51,63]. One recent study showed that the independent predictors of an unfavorable outcome 1 year after TASE onset were longer TASE duration, evidence of tumor progression at TASE onset, and absence of surgical treatment before onset.…”
Section: Management Of Tae and Tasementioning
confidence: 99%
“…Vascular studies help identify infarcts, a common cause of new status, both arterial or venous, and cavernomas. Whilst potentially a late disease feature [26], SE due to metastases and primary brain tumours can respond to anti-seizure therapy [27]. Contrast CT can also be used to identify intracranial metastasis, that account for 7% of SE.…”
Section: First-line Cranial Imagingmentioning
confidence: 99%